Collecte et évacuation des boues de vidange dans la ville de Bafoussam, Cameroun (Afrique centrale) - Célestin Defo; Théophile Fonkou; Paul Blaise Mabou; Paulin Nana; Yacouba Manjeli (VertigO)
The aim of this study is to describe the system of collection and evacuation of faecal sludge in Bafoussam (Cameroon), to raise the insufficiencies in order to propose a method for a better management. The actors and their roles in the chain of management of faecal sludge were identified. Faecal wastes were collected, characterized in the lab and their potential effects on the surrounding populations of the site of the discharge were evaluated. The principal results showed that faecal wastes are managed autonomously in the septic tanks (49 %) and the latrines (59 %). The actors involved in the collection and evacuation of faecal sludge are : population, urban community and a private company. The physicochemical characteristics of muds are very high compared to the norms of rejection required by the World Health Organization (DCO, 60 500 mg/l ; NH4+, 1472 mg/l ; PO4-3, 1044 mg/l). A volume of about 1440 m3 of faecal waste are pumped per year by tankers and are poured without treatment at the edge of the Noun river.